Isolation and partial characterization of the lipoxygenase gene in black pepper (Piper nigrum L) (Research, Society and Development, 2022)
Black pepper is a spice that have an economic importance in the world by its wide application in industry and by medicinal properties. State of Pará is one of the largest producers of these spices, but the production of this species is committed by fusariosis, that causes root rot in plant. Study of molecular biology is important by support breeding improvement of black pepper. In this work we draw the primers Lox3R and Lox3F to amplify a larger fragment of the gene lipoxygenase (Lox) in black pepper. The amplified fragment using primers drawn was sequenced. The sequence isolated has 770 nucleotides that encode 258 amino acids. This sequence was characterized by comparison in biological databases and using computational programs. The analysis with BlastX showed that sequence isolated has high similarity with lipoxygenase proteins of Persea americana, Parasponia andersonii e Vitis vinífera. We verified that Lox of black pepper has the PLAT/ LH2 domain of plant lipoxygenase related proteins. Its description in black pepper is essential to clarify the molecular mechanisms of response of the plant to the Fungus and understand its paper in activation of the defense response, once the gene Lox is activated in plant to signal its defense in a possible attack against pathogen and may be precursors of metabolic regulators.